The alternative of oral sedation for pediatric dental care - Kim, Jongbin (J Dent Anesth Pain Med, 2015)
In pediatric dentistry, chloral hydrate is habitually selected for sedation of uncooperative children. Although chloral hydrate has been used for decades, various adverse effects are reported and necessity for new alternative drugs has increased. Dexmedetomidine was approved by FDA for sedation at intensive care units (ICU) in 1999. Compared to conventional sedative drugs, dexmedetomidine has not only analgesic and sedative effects but also it barely suppresses the respiratory system. Due to these characteristics, dexmedetomidine is known as safe sedative drug for children and elderly patients. Furthermore, approved by KFDA in 2010 in Korea, the frequency of sedation using dexmedetomidine is increasing. However, due to its intravenous administration method, it was difficult to apply in pediatric dentistry. Recently, intranasal administration method was introduced which might be a new possible alternative of oral sedation. In this study, we compare the mechanisms, pros and cons of chloral hydrate and dexmedetomidine, introducing new possibilities.